Photosynthetic Performance of Zea mays integrated with Neolamarckia cadamba under climate change condition - Romia Rona, Tagang; Hollena, Nori; Walftor, Dumin; Wee, Sze Yee; Ho, Wei Seng; Mohamad Hilmi, Ibrahim (Wiley Periodicals LLC on behalf of Crop Science Society of America and American Society of Agronom, 2026)
Anthropogenic activities have increased CO2 emissions, elevating global temperatures and disrupting rainfall patterns, thus affecting crop productivity. This study examines the photosynthetic performance of Zea mays under elevated temperatures (25˚C and 30˚C) and CO2 levels (400 and 700 ppm) in two cropping systems: monoculture and an agroforestry system combining Z. mays with Neolamarckia cadamba. The experiment consisted of three water treatments: P1 (low rainfall), P2 (normal rainfall), and P3 (high rainfall), each with four replicates, giving a total of 12 pots per cropping system and 36 pots overall across the three experimental conditions. Key photosynthetic parameters measured were CO2 assimilation rate (A), stomatal conductance (Gs), transpiration rate (E), and water use efficiency. Results revealed that Z. mays in the agroforestry system under normal rainfall, 25˚C, and 700 ppm CO2 recorded the highest net assimilation rate. This is likely due to favorable microclimatic conditions provided by the tree canopy, including better moisture retention and reduced heat stress. In contrast, the lowest photosynthetic performance occurred under low rainfall (P1), higher temperature (30˚C), and ambient CO2 concentration (400 ppm). Under these stress conditions, stomatal conductance declined significantly, restricting CO2 uptake and reducing photosynthetic efficiency. These findings suggest that agroforestry systems could help mitigate the negative impacts of climate change on crop productivity. Integrating trees with crops could enhance photosynthetic performance under future climate scenarios, supporting sustainable agriculture and food security.